Analisis framing pemberitaan penangkapan juliari batubara dalam korupsi dana bansos covid-19 pada kompas.com (Faculty of Communications Science, Dr. Soetomo University, 2021)
This article purpose is to observe the news framing about the arrest of Indonesia’s Social Affairs Minister Juliari Batubara in pandemic aid corruption case published in Kompas.com. This research is a qualitative descriptive research in which the used method are three news from Kompas.com published in December 2020 by Robert N. Entmant analysis framing model. There are four main components in Entmant framing analysis: define problem, diagnose causes, make moral judgement and treatment recommendation.. the result shows that Kompas.com tried to make a positive image for Social Affairs Ministry. Kompas.com also tried to highlight another side of Juliari Batubara such as focusing in his personal wealth and his achievement prior to serving as Social Affairs Minister. There is no detail and specific news about his arrest. Kompas.com point of view is maybe influenced by third parties, one of which is the interest of media conglomerate in Indonesia. They often made ambiguous and unclear words in corruption case news to please the stakeholders. Keywords: framing analysis, corruption case news, juliari batubara, online media